Penerapan Stretching Exercise Terhadap Intensitas Nyeri Pada Pasien Rheumatoid Arthritis di UPT Pelayanan Sosial Lanjut Usia Binjai - Yazid, Budiana; Rahmadani Sidabutar, Rina (Universitas Haji Sumatera Utara, 2025)
Pain is a complaint that occurs in the elderly, as you get older you will feel pain in your joints. Pain in the joints can hinder movement. One of the chronic inflammatory diseases that attacks the musculoskeletal system is rheumatoid arthritis. This disease causes inflammation of the joint capsule. The action taken to treat rheumatoid in the elderly is the application of stretching exercises. Stretching exercises are muscle stretching exercises using certain techniques to reduce muscle tension physiologically. The aim of this research was to determine the effect of applying stretching exercises on pain intensity in rheumatoid arthritis patients at the Binjai Elderly Social Services UPT. Quasi-experimental research design with one group pre test post test. The sample for this study was 30 respondents consisting of 15 respondents in the intervention group and 15 respondents in the control group using convenience sampling. The research instruments were the Numeric Rating Scale (NRS) and stretching exercise SOP. Bivariate analysis with Wilcoxon test with p value <α (0.000 < 0.05). So H0 is rejected, which means that there is an effect of applying stretching exercises on pain intensity in rheumatoid arthritis patients at the UPT for elderly social services in Binjai. The results of this research are expected for the elderly to carry out stretching exercises correctly in accordance with the stretching exercise SOP and do it every time before the elderly start activities so that it can improve blood flow, reduce muscle tension, relax the body, increase the range of motion, provide a feeling of comfort and prevent injury physique.